Approach to Fully Substituted Cyclic Nitrones from N‐Hydroxylactam Derivatives: Development and Application to the Total Synthesis of Cylindricine C. (18th February 2019) - Hiraoka, Shobu; Matsumoto, Tsutomu; Matsuzaka, Koki; Sato, Takaaki; Chida, Noritaka
Abstract: An approach to cyclic nitrones from N ‐hydroxylactam derivatives is documented. The nucleophilic addition of an organolithium reagent to an N ‐OSEM [SEM=2‐(trimethylsilyl)ethoxymethyl] lactam forms a five‐membered chelated intermediate, which undergoes both elimination and deprotection to give a fully substituted nitrone in a one‐pot process. When combined with the N ‐oxidation of easily available chiral lactams, this method becomes especially useful for the quick synthesis of chiral nitrones in enantio‐pure form, enabling the concise total synthesis of cylindricine C.